"Anything That Can Be Traded, Will Be Traded": The Contests to Automate and Financialize Advertising Futures Markets. (September 2022) - Kininmonth, Samuel
This article explores potential advertising futures markets that may emerge from current trends of automation and financialization in digital advertising. Managing price and availability is important to advertisers for securing prices and premium inventory and to publishers for safeguarding long-term revenue. The article compares US network television's annual upfront events with adtech company the New York Interactive Advertising Exchange (NYIAX). This article contributes two primary observations. First, that buying and selling forward advertising inventory is an important, and understudied, part of advertising markets. Second, the design of infrastructures that enable adverting futures markets are social and contested. The formation and framing of forward media markets has consequences for the advertising industry at a time of critical juncture and for broader media that rely on advertising revenue.